Adaptation and validation of a scale to assess digital teaching competence in soccer coaches - Ballester-Esteve, I.; Parra-Camacho, D.; Padilla-Bautista, L.; Fernandez-Piqueras, R. (Journal of Physical Education and Sport, 2023)
Since 2015, the Union of European Football Associations (UEFA) has held a convention with the aim of updating its technical qualifications for the training of its football coaches. It has proposed widespread changes, but with a particular recommendation for the creation of a subject about New Technologies. This proposal is in line with the natural evolution of today's society and with an increasing digital presence in all professional fields. The overarching concern for quality teaching in digital competences involves, first and foremost, the necessary adoption of these digital competences by their trainers. As a result, the aim of this research is to adapt and validate a scale, previously validated in other training contexts, to assess the digital teaching competence (hereafter, DTC) of soccer coaches. The study sample consists of 612 coaches at different levels who are registered in the Football Federation of the Valencian Community (hereafter, FFCV). The sample contains a higher percentage of men (91.7%) than women (8.3%) and a mean age of 30.88 years. A confirmatory factor analysis was performed, which revealed five factors grouping 31 indicators: Information and Literacy (5 items), Communication and Collaboration (6 items), Digital Content Creation (9 items), Security (6 items) and Problem Solving (5 items). Goodness-of-Fit indicators showed adequate values: (x2 /gl=2.82); RMSA= 0.6 (Confidence Interval= 0.6-0.7); CFI=.91; IFI= .91. Reliability was tested by Composite Reliability, Cronbach's Alpha and Mean Variance Extracted values. The results of the research support the reliability and validity of the questionnaire that was adapted for the purpose of assessing the digital teaching competence of soccer coaches.